Edukasi Dampak Lingkungan Kegiatan Migas di Kelurahan Sungai Pakning Kecamatan Bukit Batu Kabupaten Bengkalis - Muhammad Ariyon; Detri Karya; Ellyan Sastraningsih; Ira Herawati; Imam Purwanto (CANANG: Jurnal Pengabdian Masyarakat, 2024)
On the one hand, the existence of the oil and gas industry is needed by humans, such as for the country’s energy and foreign exchange needs,however, on the other hand, oil and gas industry activities also have great potential to pollute the environment, such as pollution of water, soil, air, and disruption of flora and fauna biodiversity. The negative impact of oil and gas activities can certainly lead to the problems such as health, economic and socio-cultural problems which will lead to community conflict. Environmental management is very necessary so that the existence of the oil and gas industry can provide benefits and welfare for humans. Knowledge about the environmental impacts is evoked from upstream oil and gas activities is very important, because communities around oil and gas operation areas will feel both direct and indirect impacts from these oil and gas activities. Especially in remote areas or inland areas where there is still a lack of information about the potential environmental impacts of oil and gas activities. Thus, education and counseling are very necessary for communities around oil and gas working areas so that they receive information and enlightenment about the potential environmental impacts resulting from oil and gas activities. The target of community service activities is the society of Sungai Pakning Village, Bukit Batu District, Bengkalis Regency, Riau Province. The issue faced was during a location survey in Sungai Pakning sub-district, Bukit Batu sub-district, Bengkalis regency, and information from the Head of Sungai Pakning sub-district, that there was still a lack of public knowledge about the environmental impacts of oil and gas activities, so it was necessary to provide education and outreach on the environmental impacts of oil and gas in Sungai Pakning sub-district. Bukit Batu District. The solution offered by the community service proposing team is to provide material regarding knowledge of the environmental impacts resulting from oil and gas operations. The approach taken was in the form of observation, discussion and question and answer with a group of partners, formulating problems and providing solutions to problems. The results achieved by this activity are that the Sungai Apit sub-district community gained knowledge about the environmental impacts resulting from oil and gas operations and CSR programs which undertaken by PT Kilang Pertamina Internasional (PT KPI) Sungai Pakning Refinery Unit.